Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) UIN Sumatera Utara - Masdinar Sihite; Ditiya Puspita (Universitas Muhammadiyah Enrekang, 2023)
The MSME (Micro Small and Medium Enterprises) industry has enormous potential. With around 57,895,721 million businesses, or around 99.99% of all businesses in Indonesia, small and medium enterprises (MSMEs) are the majority. In terms of labor absorption, MSMEs absorbed 114,144,082 people, or around 96.99% of the workforce in Indonesia, in 2013. Corporations absorbed the remaining 3%. Most Indonesian people do micro and small businesses. This business usually has the same characteristics in each region; There is nothing good about a low exclusion rate; Several cases show that micro, small and medium enterprise groups cannot meet basic needs such as shelter, nutrition, education, health and housing.